2016
DOI: 10.21475/ajcs.2016.10.10.pne6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among cultivated and wild lentils for iron, zinc, copper, calcium and magnesium concentrations

Abstract: Information on the seed mineral concentration of cultivated and wild lentils is limited. The objective of this study was to determine the concentrations of iron (Fe), zinc (Zn), calcium (Ca), copper (Cu), and magnesium (Mg) in the seeds of 26 lentil genotypes representing 4 species and 3 subspecies of Lens. Plants were grown in a greenhouse using a completely randomized design with three replicates (n=78). Seed mineral concentrations were measured using acid digestion followed by inductively coupled plasma-opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Six annual species, namely, Cicer atlanticum , Cicer echinospermum , Cicer floribundum , Cicer graecum , Cicer isauricum , and Cicer reticulatum , are categorized as rare (R) and were included in the 1997 World Conservation Union (International Union for Conservation of Nature, IUCN) List of Threatened Plants (Walter & Gillett, 1998). The genome of cultivated chickpea ( C. arietinum , kabuli type CDC Frontiers and desi type ICC4958) and the wild progenitor ( C. reticulatum ) have been sequenced (Bajaj et al, 2015; Gupta et al, 2016; Parween et al, 2015; Varshney et al, 2013), along with resequencing of 429 accessions of elite varieties and landraces (Varshney et al, 2019). These results and previous work (Penmetsa et al, 2016) suggested that the kabuli type was derived more recently from desi type and has lower diversity.…”
Section: Chickpeamentioning
confidence: 99%
“…Six annual species, namely, Cicer atlanticum , Cicer echinospermum , Cicer floribundum , Cicer graecum , Cicer isauricum , and Cicer reticulatum , are categorized as rare (R) and were included in the 1997 World Conservation Union (International Union for Conservation of Nature, IUCN) List of Threatened Plants (Walter & Gillett, 1998). The genome of cultivated chickpea ( C. arietinum , kabuli type CDC Frontiers and desi type ICC4958) and the wild progenitor ( C. reticulatum ) have been sequenced (Bajaj et al, 2015; Gupta et al, 2016; Parween et al, 2015; Varshney et al, 2013), along with resequencing of 429 accessions of elite varieties and landraces (Varshney et al, 2019). These results and previous work (Penmetsa et al, 2016) suggested that the kabuli type was derived more recently from desi type and has lower diversity.…”
Section: Chickpeamentioning
confidence: 99%
“…However, a combination of P . vulgaris , Lens culinaris , and Glycine max would be sufficient to meet nutritional demand (data shown in Table ; Gupta et al, ; Islam et al, ; Ray et al, ; Yang et al, ). Importantly, it should be noted that the mineral content of pulses is dependent on both the cultivar grown and the nutritional composition of the soil (Hall et al, ; Wang & Daun, ).…”
Section: The Benefit Of Legumesmentioning
confidence: 99%
“…As such, the dietary inclusion of Phaseolus vulgaris alone would not be sufficient for an adult to meet their recommended daily nutritional requirements, with the average concentration of selected micronutrients in P. vulgaris (milligrams per kilogram) being calcium: 2.05; iron: 81; magnesium: 3.08; zinc: 50.5; and selenium: 0.43. However, a combination of P. vulgaris, Lens culinaris, and Glycine max would be sufficient to meet nutritional demand (data shown in Table 2; Gupta et al, 2016;Islam et al, 2002;Ray et al, 2014;Yang et al, 2003). Importantly, it should be noted that the mineral content of pulses is dependent on both the cultivar grown and the nutritional composition of the soil (Hall et al, 2016;Wang & Daun, 2004).…”
Section: Nutritional and Antinutritional Factors In Legumesmentioning
confidence: 99%
“…In an examination of a large database of 26 domesticated and wild lentil genotypes, Gupta et al (2016) found Fe, Zn, and Mg contents to range from 2 to 9, 1 to 5, and 27 to 90 mg 100 g −1 , respectively. The results from the current study were found to be commensurate, although generally on the higher end of the range (Table 3).…”
Section: Discussionmentioning
confidence: 99%